Evaluation of Water Quality of Way Kuripan’s River Using Water Quality Index Tool - Rina Febrina (Program Pascasarjana Universitas Sriwijaya, 2017)
The aim of this study is to analyze the water quality of the Way Kuripan River based on the Water Quality Index (WQI) calculation method that is developed by the Malaysian Department of Environment (DOE). Water samples were taken from five sample points (SK01, SK02, SK03, SK04 and SK05) in January 2017. WQI was calculated on the basis of six parameters: dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), pH, total suspended solid (TSS) and ammoniac-nitrogen (NH3-N). The calculation procedure consists of three stages. Firstly, identifying the equation of the sub-index (SI) based on the parameter value. Secondly, calculate the sub-index (SI) of each parameter. Last is the calculation of the water quality index. The results show that SK01 and SK04 have WQI values of 70.3 and 70.11. Those values show that water quality of the Way Kuripan river is class III so the water is slightly polluted. Sample points, SK02 (WQI = 55.8) and SK03 (WQI=53.8) are highly polluted. The lowest WQI of the Way Kuripan river is SK05 = 38.3, so it is classified as,Class V (highly polluted). In conclusion, this data confirms that the water quality in the Sungai Kuripan River has been polluted.Keywords: Way Kuripan’ s River, Water Quality Index (WQI), water quality parameter